Linguocultural Analysis of The Concept «Love» In the English Proverbs (Eurasian Research Bulletin, 2021)
Love is inherent in all human cultures. The concept Love is one of the most common and least defined concepts in modern science. It is evident that Love is essentially an abstract concept that is much easier to experience than to explain. From a position of various dictionaries, the notion “Love” can be defined as “an intense feeling of affection, emotional intimacy and shared interests and experiences are common to all people’s friendships”. In this paper, one of the ways of investigating the concept is considered by the method of analysis of the paremiological stock contains different types of proverbs.